Legal Clinics as an Important Element of Human Right for Free Legal Aid - Ківалов, Сергій Васильович; Ківалов, С. В.; Кивалов, Сергей Васильевич; Kivalov, Serhii V. (Los Hemisferios University, 2019)
Nowadays, legal clinics exist in almost every country in the world. The article examines the legal status of legal clinics in Ukraine to properly ensure the human right to legal aid. The author emphasizes that legal clinics are an important element of the legal aid institute. Accordingly, there is an urgent need to regulate the legal status of legal clinics, since in this way the state fulfills its obligation to guarantee the constitutional right of every person to receive legal aid. Even though legal clinics perform important social tasks, regulatory regulation of their activity is carried out only at the level of acts of the Ministry of Education and Science of Ukraine. All attempts to consolidate the legal status of legal clinics at the level of the law—for example, the Law “On Free Legal Aid” of June 2, 2011—remain unrealized. The author states that the issue of improving the legal regulation of relations involving legal clinics should be resolved in the near future. Moreover, the Verkhovna Rada (Ukrainain Parlament) has recently started reforming its legislation in the field of advocacy. Therefore, there is a chance that the discriminatory norm of the Constitution regarding the lawyer’s monopoly on representation in court will be abolished. Thus, this will open the way to improving the status of legal clinics, as employees of such institutions will have the opportunity, in addition to legal advice, to represent their clients in court.

Нині юридичні клініки існують практично в кожній країні світу. У статті досліджено правовий статус юридичних клінік в Україні щодо належного забезпечення права людини на правову допомогу. Автор підкреслює, що юридичні клініки є важливим елементом інституту правової допомоги. Відповідно, існує нагальна потреба у врегулюванні правового статусу юридичних клінік, оскільки таким чином держава виконує свій обов’язок гарантувати конституційне право кожної людини на отримання правової допомоги. Незважаючи на те, що юридичні клініки виконують важливі соціальні завдання, нормативне регулювання їх діяльності здійснюється лише на рівні актів Міністерства освіти і науки України. Усі спроби закріпити правовий статус юридичних клінік на рівні закону, наприклад, Закон «Про безоплатну правову допомогу» від 2 червня 2011 року, залишаються нереалізованими. Автор констатує, що питання вдосконалення правового регулювання відносин за участю юридичних клінік має бути вирішене найближчим часом. Крім того, нещодавно Верховна Рада розпочала реформування свого законодавства у сфері адвокатури. Тому є ймовірність, що дискримінаційна норма Конституції щодо монополії адвоката на представництво в суді буде скасована. Таким чином, це відкриє шлях до покращення статусу юридичних клінік, адже працівники таких установ отримають можливість, окрім юридичних консультацій, представляти інтереси своїх клієнтів у суді.
Kivalov S. Legal Clinics as an Important Element of Human Right for Free Legal Aid / S. Kivalov // Ius Humani. Law Journal. - Los Hemisferios University, 2019. - Vol. 8. - Р. ‏ 169-186.
Keywords: human rights; legal aid; legal clinic; primary legal aid; Pro Bono; права людини; правова допомога; юридична клініка; первинна юридична допомога; Pro Bono; Research Subject Categories::LAW/JURISPRUDENCE